Photoredox-Catalyzed Reductive Activation of Ammonium Salts - Jacob, Clément; Annibaletto, Julien; Theunissen, Cédric (Synlett, 2025)
The reductive activation of C–N bonds by single-electron transfer enables the generation of radicals from readily available and abundant amines. Despite their potential, such transformations remain challenging because of the stability of the C–N bond, which often requires preactivation to facilitate its cleavage. In this context, quaternary ammonium salts constitute ideal amine-derived radical precursors as they are stable and easy to handle, in addition to enabling the design of atom-economical processes. In this article, we highlight our recent work on the photoredox-catalyzed reductive activation of ammonium salts. Several ammonium salts could indeed be successfully activated using iridium photoredox catalysis, the corresponding radicals being subsequently engaged in hydrodeamination reactions and radical couplings. Moreover, the reactivity observed experimentally could be correlated to the redox potentials of the ammonium salts, which were determined by cyclic voltammetry.1 Introduction2 Hydrodeamination of Benzylic and Aryl Ammonium Salts3 Selective Activation and Extension to Radical Couplings4 Determination of the Redox Potentials of Ammonium Salts5 Conclusion
Keywords: photoredox catalysis; iridium catalysis; C–N bond activation; hydrodeamination reactions; radical couplings; ammonium salts